2022
DOI: 10.1021/acs.analchem.2c02479
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Sensitive Imaging Analysis of Cell–Microenvironment Interactions by Electrochemiluminescence Microscopy

Abstract: A complex and heterogeneous cell microenvironment offers not only structural support for cells but also myriad biochemical and biophysical cues. These outside-in signals transmit into cells primarily through integrins, which are the important components of cell–matrix adhesions to direct and maintain cell behaviors and fate. In this work, we report a surface-sensitive imaging methodology for evaluating the difference in cell–matrix adhesions at the single cell level to dissect the impact of the chemical microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Thus, they later changed the terminal groups tethered on SNM/ITO to explore the specific recognition of integrins to different surfaces. Through the morphology change of cell adhesion, it was found that α6, α5, and α1 subunits sensed SNM, RGD/OEG, and APTES electrode surfaces, respectively . Gao et al then observed the process of cell shrinking, crumpling, and detaching from the electrode surface by adding H 2 O 2 , along with the cell aggregation by electrical stimulation.…”
Section: Diverse Applications Of Ecl Microscopymentioning
confidence: 99%
“…Thus, they later changed the terminal groups tethered on SNM/ITO to explore the specific recognition of integrins to different surfaces. Through the morphology change of cell adhesion, it was found that α6, α5, and α1 subunits sensed SNM, RGD/OEG, and APTES electrode surfaces, respectively . Gao et al then observed the process of cell shrinking, crumpling, and detaching from the electrode surface by adding H 2 O 2 , along with the cell aggregation by electrical stimulation.…”
Section: Diverse Applications Of Ecl Microscopymentioning
confidence: 99%
“…44 Further modifying the SNM rich in silanol groups with Arg-Gly-Asp (RGD), (3-aminopropyl)triethoxysilane (APTES), and oligo(ethylene glycol) (OEG), the influence of chemical microenvironments on cell behaviors was evaluated by imaging the cell-matrix adhesions. 46 The statistical analysis of spatial distribution, area and strength of adhesions shows that the surfaces tethered with RGD and OEG groups can mediate the robust and weakest cell-microenvironment interactions, respectively, and that an intermediate adhesion is distributed on the APTES-coated surface. Moreover, in conjunction with selective immune-blocking of different integrin subunits, a 6 , a 5 , and a 1 subunits are found to function in recognizing SNM, RGD/OEG and APTES surfaces, respectively.…”
Section: Ecl Microscopymentioning
confidence: 99%
“…15,16 ECL microscopy has been used for imaging of cell membranes, 17,18 cell adhesion, 19,20 cell−cell junctions, 21 and the interactions between cells and the surrounding microenvironment. 22 Sojic's group recently developed shadow ECL microscopy for imaging single mitochondria, 23 which is the smallest biological object imaged by conventional ECL microscopy. However, revealing different types of biological samples, such as bacteria for identification and uncovering their specific features at the nanoscale with ECL microscopy, remains challenging.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Electrochemiluminescence (ECL) is a light emission process that is turned on by electrochemical reactions. , This process has attracted increasing attention for bioimaging at the single cell level because of its low background, high sensitivity, and ability to provide unique information on chemical characteristics such as local chemical activity in addition to spatial information. , ECL microscopy has been used for imaging of cell membranes, , cell adhesion, , cell–cell junctions, and the interactions between cells and the surrounding microenvironment . Sojic’s group recently developed shadow ECL microscopy for imaging single mitochondria, which is the smallest biological object imaged by conventional ECL microscopy.…”
Section: Introductionmentioning
confidence: 99%